Spectators involved in the work of contemporary art - Isaza Echeverry, María Isabel (Universidad Católica de Pereira, 2012)
The interest of this article aims to describe the art after avant-garde understanding from different parameters to which regulated the art object as an art of representation. Nowadays art has become the environment real and it has expanded into social and communicative actions involving the viewer in new forms of participation and action. To analyze the changing role of the viewer it was taken as main reference the concepts of game, party and symbol of Hans-Georg Gadamer as categories that help us to understand, to theorize and to approach to contemporary art. These three concepts show that contemporary art demands an active and participatory audience able to immerse themselves in the aesthetic creation.